Malaysian School Counselor’s Self-Efficacy: The Key Roles of Supervisor Support for Training, Mastery Experience, and Access to Training - Ooi, Pei Boon; Wan Jaafar, Wan Marzuki; Crosling, Glenda (Frontiers in Psychology, 2021)
The concept of self-efficacy has been widely studied and shown to contribute to individuals’ job satisfaction and organizational commitment. For counsellors, the concept measures their belief in their ability to conduct counselling sessions. However, it is an understudied area. As Bandura states, self-efficacy and its sources should be investigated and measured within its domain, which in this case is school counselling. This study examined the impact on school counsellors’ self-efficacy and job satisfaction of the personal and environmental factors: (a) mastery experience, (b) social persuasion, (c) vicarious learning, (d) physiological and affective state, (e) the access to training, and (f) perceived supervisor support of training. The cross-sectional study involved 541 Malaysian secondary school counsellors nationwide via a random sampling-distributed questionnaire. Results which were analysed using PLS-SEM, with importance-performance functionality embedded in it, indicated that mastery experience, access to training and perceived supervisor support of training explained 45.6% variance in counselling self-efficacy and together with counselling self-efficacy, contributed 13.2% variance in job satisfaction among the school counsellors. IPMA revealed supervisor support of training as of greatest importance in shaping counselling self-efficacy. Counselling self-efficacy partially mediated the relationship between mastery experience, access to training, supervisor support toward training and job satisfaction Arising from this finding is a proposed theoretical framework in which efficacy information (i.e., mastery experience), environmental determinants (i.e., access to training and supervisor support of training) and cognitive determinant (i.e., counselling self-efficacy) corresponded together congruently and lead to higher job satisfaction. Suggestions are also made for training providers, content developers and policymakers to include these factors in professional development training and continuous education, to sustain the wellbeing of school counsellors.